Description of Sinothomisus gen. nov. with a new species from Yunnan Province, China (Araneae, Thomisidae) - Tang, Guo; Yin, Chang-Ming; Griswold, Charles; Peng, Xian-Jin (Zootaxa, 2006)
This paper reports a new thomisid spider genus Sinothomisus with type species, Sinothomisus liae sp. nov., from Gaoligong Mountains, Yunnan Province, China. Photos of bodies, SEM photos of male palpal organ, illustrations of copulatory organs and the detailed morphological characteristics are given.